Preventive Legal Education and Digital Literacy on the Dangers of Online Gambling for Students of Kapuas Pontianak Private High School - Rangga, Boy; Rupita, Rupita; Arif, Ibnu; Mandala, Yoga; Zulkarnain, Zulkarnain; Ningrum Palureng, Rurika Widya; Safriadi, Safriadi; Ira, Nurmaya Putri; Ikhsan, Syarif Muhammad; Catherine, Liany Ayu; Rochman, Auliya; Teresa, Roma; Mukti, Plasma Versiana; Banjarnahor, David; Parapat, Henry Anderson; Prayudha, Tengku Andrias (STKIP Singkawang, 2025)
The problem of teenagers' involvement in online gambling practices is a crucial issue that requires educative and preventive handling. This fact has caused concern among teachers and principals of private high schools in Kapuas Pontianak. Private SMAs in Pontianak City have never received education on online gambling practices so they need it as an effort to prevent their students from participating in online gambling practices. This Community Service activity aims to provide preventive legal education and digital literacy to students of SMA Swasta Kapuas Pontianak City as an initial step to prevent online gambling practices. The methods used included interactive lectures and dissemination of educational materials. The evaluation of the activity was attended by 35 participants by providing descriptive impressions and messages and the results of the evaluation indicated an increased awareness of the risks and legal impacts of online gambling. This finding proves that an integrative approach between legal aspects and digital literacy is effective in building students' understanding and critical attitude towards digital threats. This activity is important as an educational intervention model that can be replicated in other schools, as well as developed in the form of a long-term school-based education programme on the dangers of online gambling practices.Edukasi Hukum Preventif dan Literasi Digital Tentang Bahaya Judi Online Bagi Siswa SMA Swasta Kapuas PontianakABSTRAKPermasalahan maraknya keterlibatan remaja dalam praktik judi online menjadi isu krusial yang memerlukan penanganan edukatif dan preventif. Fakta yang terjadi ini membuat kekhawatiran para guru dan kepala sekolah SMA Swasta Kapuas Pontianak. SMA Swasta Kota Pontianak belum pernah mendapatkan edukasi terhadap praktek judi online sehingga mereka memerlukan hal tersebut sebagai upaya untuk mencegah siswa dan siswi mereka ikut dalam praktek judi online. Kegiatan Pengabdian kepada Masyarakat ini bertujuan untuk memberikan edukasi hukum preventif dan literasi digital kepada siswa SMA Swasta Kapuas Kota Pontianak sebagai langkah awal pencegahan terhadap praktik judi online. Metode yang digunakan meliputi ceramah interaktif serta penyebaran materi edukatif. Evaluasi egiatan diikuti oleh 35 peserta dengan meberikan kesan dan pesan secara deskriptif dan hasil dari evaluasi tersebutpeserta mengindikasikan peningkatan kesadaran terhadap risiko dan dampak hukum dari judi online. Temuan ini membuktikan bahwa pendekatan integratif antara aspek hukum dan literasi digital efektif dalam membangun pemahaman dan sikap kritis siswa terhadap ancaman digital. Kegiatan ini penting sebagai model intervensi edukatif yang dapat direplikasi di sekolah lain, serta dikembangkan dalam bentuk program edukasi jangka panjang berbasis sekolah tentang bahaya praktek judi online.Kata Kunci :Judi online; Edukasi hukum; Literasi digital